INVESTIGATION OF THE FEASIBILITY OF ALTERNATIVE BURNOUT MATERIAL (MAIZE COB) VERSUS THE TRADITIONAL MATERIAL (SAWDUST) FOR POINT-OF- USE CERAMIC WATER FILTER PRODUCTION (Nigerian Journal of Technology, 2024)
Ceramic water filters, are a promising household water treatment technology. Filters were produced  using clay as the base material and two locally available burnout materials (sawdust and maize cob). The clay which was classified as an Inorganic clay of low to medium plasticity has a liquid limit of 41.1% and plasticity index of 37.4%. The sizes of the combustible materials are 5,10, 22 microns mixed in proportions of 1:1 and 1:2 by proportions of clay and burnout materials respectively, moulded and fired to a temperature of 1000℃. In the end, ten filters were produced from various particles sizes and proportions of the sawdust and maize cob. The bulk density of the filters ranged from 1.67 to 3.5 g/cm3 with a typical value of 2.63±0.57 g/cm3. Apparent porosity ranged from 94.94 to 99.87% with a typical value of 99.10±1.13%; while water absorption varied from 28.6 to 59.71 % with a mean of 40.02±9.49 %. Flow rate ranged from very slow rate of 0.051 to 0.92 L/h with a typical value of 0.354±0.226 L/h. Based on type of burnout material, filters made with sawdust had higher flow rates (0.433 L/hr) than those made from maize cob (0.291 L/hr). The percent turbidity removal ranged from 9.1% - 43.7% on the first week to 30.6 – 70.4% on the fifth week of the test for filters made from maize cob; whereas the percent turbidity removal ranged from 5.7 – 35.3% on the first week to 44.9 – 75.6% on the fifth day for sawdust.  Filters made from sawdust performed significantly better than those made from maize cob (p = 0.044) at 95% confidence level. In terms of particle size, there was an increase in efficiency of Coliform removal efficiency from 99.6 to 99.8% as the particle size of burnout materials increased from 5 μm to 22 μm. Filters made with lower proportion (1:1) of burnout materials exhibited higher Coliform removal (99.76%) than those made with higher (2:1) proportion (99.63%). However, the proportion of burnout materials within the range used in this study did not significantly affect percentage Coliform removal (p = 0.247). Filters made from sawdust generally performed better than those made from maize cob.